História social do comércio na Senegâmbia : espaço e agência local (1580-1700). - Felipe Silveira de Oliveira Malacco (2023)
This thesis aims, from the Social History of Commerce perspective, to seek a definition for the space of Senegambia between 1580 and 1700. For this, we will analyze the commercial activity of Senegambian, Saharan and Atlantic agents, who built the internal mercantile networks and long-distance routes connected to Senegambia. We analyze the goods that circulated in the Senegambian domestic market, seeking to comprehend how the trade affected and was affected by economic, political, social and cultural relations of the region’s context at the beginning of the Modern Age. We sought to understand how the preponderance of Senegambian political units over foreign agents was a constitutive element of the exchanges carried out in long-distance trade, as well as the need for adaptation of these foreign agents to social regulations and to market demands by Senegambian agents. The conclusion is that Senegambia was a region of “convenience and coexistence” and “complementarity and transition” for internal reasons and not based on Saharan or Atlantic demand. In this research, commerce was the “cement” that connected all this space.